Cryoablation and radiofrequency ablation during mitral valve surgery for rheumatic mitral valve disease: a retrospective cohort study - Nurbay, Zhanar; Dzhumabekov, Auyeskhan; Kuanishbekova, Roza; Tuleutayev, Rustem; Musrepov, Nurzhan (Frontiers in Cardiovascular Medicine, 2026)
Background and aimsAtrial fibrillation (AF) frequently accompanies rheumatic mitral valve disease (MVD) and adversely affects postoperative outcomes. Radiofrequency ablation (RFA) and cryoablation are commonly used during mitral valve surgery, but their comparative impact on atrial remodeling in this population remains uncertain.MethodsThis retrospective cohort included 100 patients with rheumatic MVD and persistent AF who underwent mitral valve surgery with concomitant cryoablation (n = 50) or RFA (n = 50) between June 2020 and June 2024 at centers in the Almaty region, Kazakhstan. Clinical and echocardiographic parameters were assessed preoperatively, within 48 h postoperatively, and at 6 ± 2 months.ResultsCryoablation was associated with greater left atrial (LA) volume reduction immediately and at follow-up (both p < 0.001). Multiple linear regression identified ablation modality as the only independent predictor of LA volume reduction (β = 27.9 mL, p < 0.0001), whereas duration of rheumatic disease, BMI, EuroSCORE II, and AF recurrence were not significant. At follow-up, the reduction in right atrial short-axis diameter was smaller after cryoablation (p = 0.049), and stroke volume declined less compared with RFA (–1.2 ± 17.3 mL vs. −7.3 ± 15.8 mL; p = 0.006). Cardiopulmonary bypass time, aortic cross-clamp time, and postoperative symptom improvement were comparable between groups. Freedom from AF during follow-up was also similar (log-rank p = 0.52).ConclusionsIn patients with persistent AF and rheumatic MVD undergoing mitral valve surgery, cryoablation was associated with more pronounced early atrial reverse remodeling and better preservation of stroke volume compared with RFA, without differences in operative efficiency or short-term safety. These findings should be considered hypothesis-generating, and prospective randomized studies with standardized lesion sets are required to confirm modality-specific effects.